2015
DOI: 10.1002/advs.201500027
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering and Design Strategy for Surface‐Amorphized TiO2@Graphene Hybrids for High Power Li‐Ion Battery Electrodes

Abstract: Surface amorphization provides unprecedented opportunities for altering and tuning material properties. Surface‐amorphized TiO2@graphene synthesized using a designed low temperature‐phase transformation technique exhibits significantly improved rate capability compared to well‐crystallized TiO2@graphene and bare TiO2 electrodes. These improvements facilitates lithium‐ion transport in both insertion and extraction processes and enhance electrolyte absorption capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(105 citation statements)
references
References 28 publications
4
101
0
Order By: Relevance
“…Ultrathin 2D materials have been explored for photocatalysis due to their intriguing properties including large interlayer space, ultrahigh surface area, and tunable electronic properties ,. In particular, the open surface potentially provide additional shortened paths for electric transport, while the atomic defects induced by oxygen vacancies trigger unexpected changes in electronic states, consequently affording higher charge mobility . For example, Yi Xie's group for the first time demonstrated that ultrathin BiOCl nanosheets could enhance the photocatalytic degradation of organic dyes due to effective separation of photoinduced electron‐hole pairs .…”
Section: Figurementioning
confidence: 99%
“…Ultrathin 2D materials have been explored for photocatalysis due to their intriguing properties including large interlayer space, ultrahigh surface area, and tunable electronic properties ,. In particular, the open surface potentially provide additional shortened paths for electric transport, while the atomic defects induced by oxygen vacancies trigger unexpected changes in electronic states, consequently affording higher charge mobility . For example, Yi Xie's group for the first time demonstrated that ultrathin BiOCl nanosheets could enhance the photocatalytic degradation of organic dyes due to effective separation of photoinduced electron‐hole pairs .…”
Section: Figurementioning
confidence: 99%
“…To mitigate this issue, doping of a nonmetal element such as F, S, or N into TiO 2 has shown improved performance . The improvement is generally attributed to structural modulation rather than surface functionalization, although surface functionalization has been proven a key approach in the realization of high electrochemical activity …”
mentioning
confidence: 99%
“…Li 4 Ti 5 O 12 has been widely studied in recent years, owing to its high discharge voltage platform (1.5 V),l ong cycle life, and excellent thermals tability. [4][5][6] Especially,t he high discharge voltage effectively restricts the formation of SEI film to avoid potentials ecurity issues. However,l ow theoretical capacity (175 mAh g À1 )s everelyl imits its practical application.…”
Section: Introductionmentioning
confidence: 99%